2010
DOI: 10.7150/ijms.7.278
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-media thickness in childhood and adolescent obesity relations to abdominal obesity, high triglyceride level and insulin resistance

Abstract: Aim: To investigate risk factors which impact on common carotid artery intima media thickness (IMT).Methods: A total of 86 obese children and adolescents and 22 healthy children and adolescents with normal weight were enrolled. Moreover, 23 of 86 obese children and adolescents were diagnosed with metabolic syndrome (MetS). The clinical, biochemical data and the IMT of the common carotid artery were measured in all subjects.Results: Obese and obese with MetS subjects demonstrated a significantly (p < 0.01) thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 24 publications
6
38
1
5
Order By: Relevance
“…Age, BMI, triglycerides and CRP are the main determinants of carotid IMT increase, as demonstrated by multiple regression analysis. These results were not in agreement with literature [25][26][27][28]. Kelishadi et al [25] found a direct, positive correlation (r = 0.27, p b 0.05) between cIMT and HOMA index among their 35 obese children and adolescent.…”
Section: Discussioncontrasting
confidence: 60%
“…Age, BMI, triglycerides and CRP are the main determinants of carotid IMT increase, as demonstrated by multiple regression analysis. These results were not in agreement with literature [25][26][27][28]. Kelishadi et al [25] found a direct, positive correlation (r = 0.27, p b 0.05) between cIMT and HOMA index among their 35 obese children and adolescent.…”
Section: Discussioncontrasting
confidence: 60%
“…31 High triglyceride levels and the IR index (HOMA-IR) were strong, independent predictors of increased carotid intima-media thickness, which was a non-invasive measure of subclinical atherosclerosis in paediatric research. 32 Nevertheless, low HDL cholesterol level carried an even greater relative risk than high triglyceride levels. 33 Compared with those without AN, subjects with the condition had a higher mean triglyceride level (P<0.001) but lower HDL level (P<0.001), and hence their future cardiovascular health seems to be of great concern.…”
Section: Discussionmentioning
confidence: 99%
“…La obesidad, según IMC, en nuestro estudio no se asoció con incremento de CIMT, a diferencia de otros estudios mencionados en el párrafo anterior. El PC tampoco se asoció aunque se ha demostrado su habilidad diagnóstica para el riesgo cardiovascular en niños y adultos [30][31][32] . Para ambos casos es posible que con un tamaño muestral mayor se relacionen con CIMT.…”
Section: Discussionunclassified